Upaya Meningkatkan Hasil Belajar IPAS Menggunakan Bahan Ajar Digital untuk Siswa - Suhendra, I Wayan; Arnyana, Ida Bagus Putu; Candiasa, I Made (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – Covid-19 has had a negative impact on the education sector. Students' understanding of the lesson material becomes less in-depth. As a result, learning outcomes do not match expectations. However, students' diverse learning styles pose a challenge in increasing students' understanding of a lesson material. For this reason, innovation is needed that can accommodate various student learning styles. The solution is to develop digital-based teaching materials that are integrated with various media variants in them.Methods – This research and development aims to determine the design, validity, practicality and effectiveness of digital-based science and science teaching materials on cognitive learning outcomes for Class IV elementary school students. The development model used is the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation" in English.Findings – Material validation received a score of 4.8 with a very high validity category, while media validation received a score of 4.5 with a very high validity category. For the practicality test, this digital science teaching material received a score of 1.75 with an excellent classification. The effectiveness test was seen based on the average normality gain which obtained a value of 0.80 in the high effectiveness category.Research Implications – From the results recorded in this research, digital-based science and science teaching materials are suitable for implementation in the learning of fourth-grade elementary school students. The validity, practicality and effectiveness proven through various trials and tests provide strong support for the educational value that can be obtained through the use of these teaching materials. Further implementation of these teaching materials can make a positive contribution to improving the quality of learning and student learning outcomes.